Human Capital Development: Efforts at Enhancing the Teaching and Learning of Science and Mathematics in Nigeria - Obilor, Isaac Esezi (Mediterranean Journal of Social Sciences, 2012)
This paper reviewed the Human Capital Development in Science and Mathematics in Nigeria. The teacherhas been identified as the most important factor in meeting the Human Capital Needs of Nigeria inMathematics, Science and Technology (MST). Thus the country’s goal of becoming one of the 20 greatestcountries of the world by the year 2020 must adequately focus on the teacher. The Teaching Profession isat the peak of all professions - it is the profession that creates other professions. All the efforts of theFederal Government of Nigeria, STAN, MAN, and other organisations have not eradicated the acuteshortage of mathematics and science teachers. It is recommended that putting back the TeachingProfession at the pinnacle it used to be in Nigeria (The Teaching Profession is at the pinnacle and hasalways been at the pinnacle in other parts of the world), will check the exodus of trained teachers. Thisway, the leakages being experienced in the profession would be eliminated and the Human Capital Needsof Nigeria in Mathematics, Science and Technology met with minimal efforts.